1992
DOI: 10.1029/92gl00579
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of thermally cracked granite

Abstract: Permeability of granite specimens heated up to 650°C were measured in the laboratory with respect to both confining and pore pressure. An unexpected behavior (permeability decrease) was found in the low temperature range (20–125°C). Permeability variations are interpreted with the help of a theoretical model of porosity. Complementary measurements of porosity and absolute surface area have also been obtained. A discussion in terms of microstructural controlling parameters concludes to a decrease of crack apert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 8 publications
5
45
0
1
Order By: Relevance
“…The decrease in permeability was due to the closure of inclined cracks by the elastic and viscous deformation enhanced by temperatureconfining-pressure coupling. Thermal elastic expansion of mineral particles can be another cause of further crack closure at 353 K [Darot et al, 1992]. The elastic deformations, however, was not observed in the thin-section images, because they were prepared after unloading.…”
Section: The Mechanisms Of Permeability Change By Consolidationmentioning
confidence: 97%
“…The decrease in permeability was due to the closure of inclined cracks by the elastic and viscous deformation enhanced by temperatureconfining-pressure coupling. Thermal elastic expansion of mineral particles can be another cause of further crack closure at 353 K [Darot et al, 1992]. The elastic deformations, however, was not observed in the thin-section images, because they were prepared after unloading.…”
Section: The Mechanisms Of Permeability Change By Consolidationmentioning
confidence: 97%
“…Skoczylas & Henry, 1995). The importance of the issue in question (i.e., of the temperature-induced changes in rock permeability) has been repeatedly stressed by such authors as Heard and Page (1982), Vogele and Brace (1985), Darot et al (1992), Lin and Daily (1990), and Danek et al (2001). All of them also referred to the impact of thermal fractures on broadly defined filtration properties of a rock.…”
Section: Introductionmentioning
confidence: 99%
“…0094-8276/00/1999GL008414505.00 Poitiers (W France) (Darot et al, 1992;Turpault, 1989); it is composed of 40% plagioclase, 26% Kfeldspar, 24% quartz and 10% biotite. Prior to Vp measurements, cracks were generated in the cores by means of a controlled thermal treatment at room pressure, which consisted in a slow heating (løC/min) up to a plateau temperature held for 30 minutes and next followed by a slow cooling (løC/min) down to room temperature.…”
Section: Paper Number 1999gl008414mentioning
confidence: 99%
“…The aim of the thermal pre-treatment is to generate different crack populations in the starting material. Previous work on La Peyratte granite (Darot et al, 1992) has shown that above 120øC, the induced residual thermal damage results in a progressive increase of the connected porosity and permeability. It has been shown that Vp depends on the intensity of the damage induced by the thermal treatment whereas Vp anisotropy was found to be very weak, if any in thermally treated samples Men6ndez et al, 1999).…”
Section: Introductionmentioning
confidence: 99%